Response of maize (Zea mays) to phosphorus application on basaltic soils in Northwestern Cameroon - Osiname, O.; Meppe, F.; Everett, L. (2000)
A field trial was conducted on two P sorptive, basaltic soils commonly used for maize production in Northwestern Cameroon. The objective was to determine the maintenance P rates required for adequate P supply in the soils for maize after initial capital dressing applications of P (0, 22, 44, 88 and 132 kg ha-1) in 1991. These were followed by three supplementary P rates – 0, 44 and 88 kg ha-1 in 1992. Three crops of maize (cv COCA) were grown to monitor the availability of the residual P. Experimental design was randomized complete block with four replications in 1991 and a split-plot in 1992 and 1993. The soils at the experimental sites were rich in organic P which formed 67% and 57% of total P at Mfonta and Babungo respectively. Laboratory P sorption studies indicated high P requirements by the basaltic soils used in the study. The amounts of P sorbed to attain 0.2 ug g-1 in soil solution were 1200 ug g-1 at Mfonta and 600 ug g-1 at Babungo. In spite of these high P sorption capacities, significant responses to small rates of P application were observed. It was concluded that a sizable proportion of P released from organic P mineralization was used to satisfy P sorption capacity of the soils, resulting in maize response to small rates of fertilizer P application. Residual P effects on maize yield were related to applied P. Bray 1 extractable soil P was weakly related to grain yields (r = 0.136 at Mfonta and r = 0.186 at Babungo). A critical value of 5.5 mg kg-1 Bray 2 extractable P in the soil was established for maize at Mfonta site. About 44 kg P ha-1 was recommended for maize at this site when Bray 2 soil P test was below this critical value.